Musical Art and Preferences in Ukraine: Psychological Influences on Youth Social Consciousness - Broiako, Nadiia; Dorofieieva , Veronika; Sinelnikov, Іvan; Ovcharenko , Svіatoslav; Kovmir , Nataliia (Universitas Negeri Semarang, 2025)
During the war and reconstruction, musical art in Ukraine has become an effective vehicle for emotional expression, identity formation, and national resistance. Ukrainian music, in its traditional and modern forms, is responsive to the country’s political and psychological circumstances, making it essential to comprehend its impact on public consciousness and cultural transformation. A cross-sectional study of 368 Ukrainian youth aged 18-25 across five regions (West, South, Central, East, and North) evaluated psychological traits using the PANAS-SF, Sense of Coherence (SOC-13), and Social Dominance Orientation (SDO) scales. Musical preferences were rated on 19 different genres. Exploratory Factor Analysis (EFA) in each region was employed to uncover underlying dimensions in psychology. Regional factor models uncovered different psychological constellations. Across all regions, music was invariably correlated with ideological orientation or emotional resilience, underscoring its cohesive psychological function during crises. Musical art in Ukraine serves as something more significant than aesthetic representation - it serves as a psychological anchor, cultural icon, and act of civil resistance.